Activation of silent synapses driven by emerging technologies: mechanisms, disease associations, and prospects for clinical translation - Yongli Li; Yong Liao; Shouyao Zhang; Chenggui Xu; Ruhua Lan; Pengbin Zhao; Ruilu Liu; Yongli Song; Xinghe Zhang (Frontiers in Synaptic Neuroscience, 2026)
Silent synapses represent a unique class of synaptic connections that are non-functional at rest but possess the potential to become functional, serving as a critical reservoir for neural plasticity. Their activation mechanisms not only challenge traditional models of synaptic maturation but also provide novel insights into brain function regulation and disease pathology. This article provides a systematic review of the regulatory mechanisms underlying silent synapse activation, encompassing pre-synaptic calcium signaling-mediated vesicle cycling and active zone (AZ) optimization, post-synaptic α -amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) membrane insertion and post-synaptic density protein 95 (PSD-95) anchoring, Mg 2+ blockade release by N-methyl-D-aspartate receptor (NMDAR), as well as synergistic integration of upstream signaling pathways. Additionally, it explores the roles of astrocytes, epigenetic modifications, ubiquitin-proteasome systems, and autophagy-lysosomal systems in multi-level regulatory processes. Notably, abnormal regulation of silent synapses exhibits two contrasting pathological patterns in diseases: “desilencing impairment” (e.g., Alzheimer’s disease, depression) and “abnormally excessive desilencing” (e.g., drug addiction, chronic pain), which establishes a theoretical framework for targeted interventions. The study further evaluates the applicability and limitations of emerging technologies—including high-resolution imaging, single-cell omics, optogenetics, and AI-driven brain-inspired computing—in silent synapse research, while systematically summarizing clinical advancements, current challenges, and future directions, aiming to inform both fundamental neuroscience studies and therapeutic interventions.